Investasi Digital: Faktor Penentu dalam Keputusan Investasi - Fahri Ali Ahzar; Rina Sari Qurniawati; Yulfan Arif Nurohman (AMIK Jakarta Teknologi Cipta Semarang, 2023)
Digital investment is a new trend in the investment world. Information technology improvement make digital investments growing rapidly. Investors warmly welcome digital investment as an alternative solution to financial problems due to the COVID-19 pandemic. This study aims to examine the effect of financial literacy, risk perception, locus of control and over confidence variables on digital investment decisions. The research was conducted in Sukoharjo Regency with a total of 100 respondents. The data collection method used a questionnaire determined by the selection of respondents through purposive sampling. The test results using SPSS software version 16.0 show that risk perception, locus of control and over confidence have no effect on digital investment decisions, while financial literacy has a positive effect on digital decisions, especially the younger generation. Young investors who do not have long experience in investing decide to invest on the basis of their financial management skills